2018
DOI: 10.1038/s10038-018-0447-6
|View full text |Cite
|
Sign up to set email alerts
|

Dysosteosclerosis is also caused by TNFRSF11A mutation

Abstract: Dysosteosclerosis (DOS) is a form of sclerosing bone disease characterized by irregular osteosclerosis and platyspondyly. Its mode of inheritance is autosomal recessive. SLC29A3 mutations have been reported as the causal gene in two DOS families, however, genetic heterogeneity has been suggested. By whole-exome sequencing in a Turkish patient with DOS, we found a novel splice-site mutation in TNFRSF11A. TNFRSF11A mutations have previously been reported in two autosomal dominant diseases (osteolysis, familial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…The results suggest that the TNFRSF11A ‐associated dominant disorders characterized by enhanced bone resorption are induced by monoallelic gain‐of‐function mutations, whereas OP‐AR7 is caused by biallelic loss‐of‐function mutations. Recently, we reported the first splice‐site mutation of TNFRSF11A (c.616+3A>G) in DOS . The variant c.784G>T identified in this study seemed to be a nonsense mutation at first glance, but was actually a splicing mutation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The results suggest that the TNFRSF11A ‐associated dominant disorders characterized by enhanced bone resorption are induced by monoallelic gain‐of‐function mutations, whereas OP‐AR7 is caused by biallelic loss‐of‐function mutations. Recently, we reported the first splice‐site mutation of TNFRSF11A (c.616+3A>G) in DOS . The variant c.784G>T identified in this study seemed to be a nonsense mutation at first glance, but was actually a splicing mutation.…”
Section: Discussionsupporting
confidence: 66%
“…However, the serum osteoclast marker TRACP‐5b was within the normal range in this patient. Similarly, the serum osteoclast maker CTX (130 pg/mL; normal range, 25 to 573 pg/mL) was also normal in the first case reported previously by us . The inconsistent result between serum osteoclast makers and in vitro osteoclastogenesis assays suggests that the mutation effect on osteoclast differentiation is mild and tends to be compromised by in vivo factors to some extent.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…But studies also showed an opposite function in some other types of cancer [39]. The tumor necrosis factor receptor superfamily member 11a (TNFRSF11A) is the receptor for RANK ligand (RANKL) and part of the RANK/RANKL/OPG signaling pathway that regulates osteoclast differentiation and activation [40]. The vasoactive intestinal peptide receptor-1 (VIPR1) has an important neuropeptide that controls lung physiology and main functions.…”
mentioning
confidence: 99%
“…A rare osteoclast-poor form of osteopetrosis, called dysosteosclerosis (DOS), accompanied by red violet macular atrophy, platyspondyly and metaphyseal osteosclerosis, is caused by mutations of the SLC29A3 (solute carrier family 29 member 3) gene encoding for a lysosomal nucleoside transporter highly expressed in myeloid cells (21, 55). More recently a novel splice-site mutation in the intron 6 of TNFRSF11A has been described in one patient indicating TNFRSF11A as additional gene responsible for DOS (56).…”
Section: Autosomal Recessive Osteopetrosis (Aro)mentioning
confidence: 99%